Edukasi Kesehatan Tentang Osteoartritis dan Pemeriksaan Kekuatan Otot pada Lansia Gratis di Posyandu Lansia - Dwi Lestari Mukti Palupi; Mustain Mustain (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
The elderly experience declines in physical and biological functions, including a high risk of degenerative joint diseases such as osteoarthritis, which can cause disability. This community service activity aims to increase elderly knowledge regarding osteoarthritis and perform early detection screenings through muscle strength examinations at the Posyandu Lansia (Elderly Health Post) in the Serengan area, Surakarta. The method used was an educational-participatory approach integrating health education using leaflets and PPT, demonstrating elderly gymnastics through videos, and conducting direct muscle strength screening. The program's effectiveness was evaluated using a structured questionnaire with a pre-test and post-test design among 30 elderly respondents. The results showed a significant increase in knowledge, with the average score rising from 33.6% (pre-test) to 85.9% (post-test), indicating an average improvement of 52.3%. The highest increase was observed in the indicator of understanding osteoarthritis complications (56.5%). Furthermore, this activity successfully initiated social change, marked by the collective awareness of Posyandu cadres to establish osteoarthritis education and elderly gymnastics as a routine monthly program. Structured health education is proven effective in improving the understanding and independence of the elderly and empowering cadres as local leaders in the community.